Differential expression of miRNAs in milk exosomes of cows subjected to group relocation. (February 2019) - Colitti, Monica; Sgorlon, Sandy; Licastro, Danilo; Stefanon, Bruno
Abstract: This study examined microRNA (miRNAs) expression and regulatory patterns from milk exosomes of cows experienced group relocation, a common husbandry practice during the lactation period and used as a spontaneous model of stress. Total RNA from milk exosome samples was collected from 3 cows that showed an increased milk cortisol (HRC) after relocation (T2 vs T1) and 3 cows that did not show cortisol increase (LRC). A total of 69 known miRNAs were identified. Thirteen miRNAs were consistently down-regulated at T2 in comparison to T1, such as miR-2904-1, miR-142, miR-2284x and miR-30b-3p. Only two miRNAs, miR-2284z and miR-146a were significantly different between LRC and HRC group. Functional enrichment analyses highlighted that glucocorticoid receptor signaling and neurotrophic factor mediated TRK receptor signaling were among the biological pathways affected by differentially expressed miRNA target genes. Mir-135a-5p and miR-320a were involved in both biological pathways. miR-142-5p, miR-142-3p, miR-30b-5p and miR-320a shared the same target genes belonging to the RAS superfamily of small GTP-binding proteins (RAC1, RAP1A and RASA1), involved in neurotrophin-mediated cell survival. MiR-142, miR-135 and miR-320a in milk exosomes were the most responsive to group relocation of cows. Highlights: Cow relocation affect milk cortisol concentration. miRNAs expression in milk exosomes senses environmental stressor. miR-142a, miR-135, miR-320a in milk as markers of stressor need to be validated.